Respuesta :

Given:

The expression are:

[tex]3x^2+7x-6[/tex]

[tex]2x^2+7x+3[/tex]

To find:

The HCF of the given expression.

Solution:

We have,

[tex]3x^2+7x-6[/tex]

[tex]2x^2+7x+3[/tex]

The factor form of given expressions are:

[tex]3x^2+7x-6=3x^2+9x-2x-6[/tex]

[tex]3x^2+7x-6=3x(x+3)-2(x+3)[/tex]

[tex]3x^2+7x-6=(x+3)(3x-2)[/tex]

Similarly,

[tex]2x^2+7x+3=2x^2+6x+x+3[/tex]

[tex]2x^2+7x+3=2x(x+3)+1(x+3)[/tex]

[tex]2x^2+7x+3=(x+3)(2x+1)[/tex]

From the factor forms it is clear that the factor [tex](x+3)[/tex] is common.

Therefore, the HCF of given expressions is [tex](x+3)[/tex].

ACCESS MORE